G258(P) A twelve month review of paediatric intensive care in myanmar to guide service development. (27th April 2015) - Halbert, J; Martin, L; Zaw, T; Rivera, RT Vasquez
Abstract : Aims: Reliable healthcare statistics are limited in Myanmar. This study aims to describe the typical patient journey through a Paediatric Intensive Care Unit (PICU) and provide vital information to guide future development. Methods: A retrospective review of the PICU admission records and patient medical notes was undertaken for all patients admitted to the PICU from 1st November 2011 until 31st October 2012. Patient information was anonymised and key data was extracted including basic demographics, history of presenting complaint, investigations, management and outcome on the PICU. Results: The PICU had 10 beds, 7 ventilators and 1 haemodialysis machine. There was a shortage of staff with only 1 doctor and 2 nurses at night. Routine investigations were available although microbiology culture was rarely performed. 407 patients were admitted with the majority being infants (range 0–16 years). The furthest distance travelled was 907Km for a child with lead poisoning. Most patients were admitted for less than 5 days. The peak admission period was during the rainy season which corresponds to the peak incidence of dengue. 64 patients (17.5%) presented with dengue shock syndrome or dengue haemorrhagic fever. The principle reasons for admission included status epilepticus (26.5%); pneumonia (20%); dengue (17.5%); multi-organ failure (14.2%); septicaemic shock (11.7%); and encephalitis (9.5%). Other important reasons for admission were meningitis; gastroenteritis; post-measles complications; diphtheria; snake bite; Beriberi (including Wernicke's encephalopathy); tetanus; rabies; malaria; late haemorrhagic disease of the newborn; malnutrition; tuberculosis; HIV; and poisoning (organophosphates; traditional medicine). All patients with a viper bite died of complications including shock, acute renal failure and pulmonary haemorrhage. The majority of patients with diphtheria were managed with a tracheostomy. Overall mortality on the PICU was 34%. Conclusions: This study provides a unique insight into the local disease burden, resources available and challenges faced in providing paediatric intensive care. The relatively high incidence of vaccine preventable diseases is of particular concern. Key priorities include support for the development of nurse and doctor training; staff retention; evidence-based guidelines; data management including follow-up; referral pathways; access to routine investigations; and a reliable supply of essential medications and equipment.